Diagnostic Performance of a Blood Urea Nitrogen to Creatinine Ratio-based Nomogram for Predicting In-hospital Mortality in COVID-19 Patients - Liu Q; Wang Y; Zhao X; Wang L; Liu F; Wang T; Ye D; Lv Y (Dove Medical Press, 2021)
Qingquan Liu,1,* Yiru Wang,1,* Xuecheng Zhao,2 Lixuan Wang,2 Feng Liu,3 Tao Wang,4 Dawei Ye,5 Yongman Lv1,2 1Department of Nephrology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan 430030, People’s Republic of China; 2Department of Health Management Centre, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan 430030, People’s Republic of China; 3Department of Urology, Shaoyang Central Hospital, Shaoyang 422000, People’s Republic of China; 4Department of Respiratory and Critical Care Medicine, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan 430030, People’s Republic of China; 5Department of Internal Medicine, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan 430030, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yongman Lv; Dawei YeTongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, No. 1095 Jiefang Avenue, Wuhan 430030, People’s Republic of ChinaTel +86-2783662848; +86-2783663409Fax + 86-2783662848Email lvyongman@126.com; dy0711@gmail.comBackground: The novel coronavirus disease (COVID-19) is leading to high morbidity and mortality. This aim of this study was to test whether blood urea nitrogen-to-creatinine ratio (BCR) is a predictor for mortality in patients with COVID-19.Methods: Ranges of “normal” BCR values were calculated from 9165 healthy subjects, and 337 and 79 COVID-19 patients were randomly assigned to the training cohort and the validation cohort, respectively. Prognostic factor of death incidence was selected by LASSO regression analyses. The prognostic ability of BCR range was assessed by logistic regression analysis. A nomogram for predicting in-hospital mortality based on BCR was developed. The performance of the nomogram was evaluated with respect to its calibration, discrimination, and clinical usefulness.Results: Among 337 COVID-19 patients, 13.4% and 11.3% were classified into higher and lower than normal range group, respectively. Kaplan–Meier curves for all-cause mortality showed that patients with higher BCR group had worse prognosis (P< 0.0001). BCR above the normal range was independently associated with death in COVID-19 patients (OR: 7.54; 95%CI: 1.55– 36.66; P=0.012). The nomogram had good discrimination in the training cohort (C-index 0.838; 0.795– 0.880) and the validation cohort (C-index 0.929; 0.869– 0.989), and good calibration. Using maximum Youden index, the cutoff values of 59.8 points, the sensitivity and specificity were 75.4% and 81%. Decision curve and clinical impact curve analysis demonstrated that the nomogram was clinically useful.Conclusion: BCR was a useful prognostic factor for COVID-19 patients. Development of an individualized BCR-based prediction nomogram can effectively predict the risk of mortality and help clinicians to make individual treatment early.Keywords: blood urea nitrogen, creatinine, coronavirus, COVID-19